Pinned-flags of some operations on fuzzy subgroups - B. B. Makamba; V. Murali (International Journal of Mathematics and Mathematical Sciences)
Fuzzy subgroups of finite groups have been treated recently using the concept of pinned-flags. In this paper, we consider the operations of intersection, sum, product, and quotient of fuzzy subgroups of finite abelian groups in general, in terms of pinned-flags. We develop algorithms to construct pinned-flags of fuzzy subgroups corresponding to these operations and prove their validity. We illustrate some applications of such algorithms.